Electro-oxidation competency of palladium nanocatalysts over ceria–carbon composite supports during alkaline ethylene glycol oxidation. Issue 2 (2nd January 2019) - Sankar, Sasidharan; Watanabe, Naoto; Anilkumar, Gopinathan M.; Nair, Balagopal N.; Sivakamiammal, Sailaja G.; Tamaki, Takanori; Yamaguchi, Takeo
Abstract : The effect of varying Pd–CeO2 ratios on the oxidation efficiency of ethylene glycol and low molecular weight alcohols in alkaline medium. Abstract : Direct alcohol fuel cells (DAFCs) are widely regarded as one of the most promising among the futuristic and capable energy systems; direct liquid fuel cells (DLFCs). In this article, we discuss in detail the competency of palladium nanoparticles developed over carbon–ceria composite supports (Pd/C–CeO2 ) as efficient and durable anode catalysts for the alkaline electro-oxidation of ethylene glycol (EGOR). For the first time, a systematic assessment of the EGOR performance of palladium catalysts with varying Pd–ceria ratios has been reported. The scalable solid-solution route reduction technique enabled the processing of Pd nanoparticles with controlled morphology, size and excellent CeO2 interaction. The structural features of the prepared catalysts were studied using X-ray diffraction, electron microscopy (TEM) and X-ray photon spectroscopy techniques, while the electrochemical performance of the catalysts was analyzed using cyclic voltammetry and chronoamperometry. During alkaline EGOR, the Pd/C–CeO2 catalysts showed an enhanced current density (as high as 68.5 mA cm −2 ), more negative onset potential, excellent mass activity (4.6 A mg −1 Pd ) and exceptional durability compared to Pd/C. The enhanced alkaline EGOR kinetics of the Pd/C–CeO2 catalysts is well attributed to the promotion effect of CeO2 on Pd by creating more Pd–OHads and also improved tolerance to poisoning species on the Pd surface. Further, the enhanced ECSA of Pd/C–CeO2 has also aided the excellent EGOR activity in alkaline medium. The validated enhanced oxidation ability of these Pd/C–CeO2 catalysts for the anodic oxidation of other low molecular weight alcohol fuels including methanol and ethanol showcased their application potential toward DMFCs and DEFCs.